The Economics of Financial Stress - Dmitriy Sergeyev; Chen Lian; Yuriy Gorodnichenko (Institute of Labor Economics (IZA), 2023)
We study the psychological costs of financial constraints and their economic consequences. Using a representative survey of U.S. households, we document the prevalence of financial stress in U.S. households and a strong relationship between financial stress and measures of financial constraints. We incorporate financial stress into an otherwise standard dynamic model of consumption and labor supply. We emphasize two key results. First, a psychology-based theory of poverty traps requires two equally important components: financial stress itself and naivete about financial stress. Specifically, sophisticates save enough to escape high-stress states, because they understand that doing so alleviates the economic consequences of financial stress. On the other hand, naifs dis-save, fall into a poverty trap, and incur high welfare losses. Second, the financial stress channel can reverse the counterfactual negative wealth effect on labor supply because relieving stress frees up cognitive resources for productive work. Financial stress also has macroeconomic implications on wealth inequality and fiscal multipliers.
Keywords: E7; G5; 330; household finance; survey; stress; behavioral economics